MODELISASI RAK PENATAAN BARANG DENGAN TEKNIK PENGGABUNGAN KOMPONEN-KOMPONEN PENYANGGA DAN TIANG RAK - Astuti, Puji; Kusno, Kusno (Prosiding Seminar Matematika dan Pendidikan Matematik, 2014)
The shape and appearance of the rack storage is most commonly manufactured in its permanently affixed form. The impacts are: heavy stuff, take up much space, difficult to move during disassembly, and the mobilization of the component and viewing angle are limited. With that limitation, it is necessary to develop rack storage model with combination of two components, namely: supporting and pole, in order this model can be built with the disassembly of its components. There fore the purpose this research is to obtain a model of the rack storage through various forms of support and pole rack so that in the end, our rack storage would be able to work with multi-function capability and flexibility, and its function is properly used in accordance with the position of the room.